1994
DOI: 10.1007/bf00022163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genetic control of germination-emergence responses of grain sorghum to salinity

Abstract: When grain sorghum is grown in saline soils, one cause of low yield is poor crop establishment. The objectives of this study were to assess the response of grain sorghum to salinity in the germination-emergence stages, study the inheritance of salt tolerance at this stage, and determine the relative contribution to final emergence of salt effects during imbibition, and after onset of germination . Twelve inbred lines and 18 F1 hybrids, resulting from an incomplete 6 x 6 factorial mating design, were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…It is considered relatively more salt tolerant than maize, the cereal crop ranking first in productivity globally (Maas, 1985). Therefore, sorghum has a good potential for salt affected areas (Ayers & Westcott, 1985;Igartua et al, 1994). There are limited successes in enhancing crop yields under salinity stress as available knowledge of the mechanisms of salt tolerance has not been converted into useful selection criteria to evaluate a wide range of genotypes within and across species.…”
Section: Sorghummentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered relatively more salt tolerant than maize, the cereal crop ranking first in productivity globally (Maas, 1985). Therefore, sorghum has a good potential for salt affected areas (Ayers & Westcott, 1985;Igartua et al, 1994). There are limited successes in enhancing crop yields under salinity stress as available knowledge of the mechanisms of salt tolerance has not been converted into useful selection criteria to evaluate a wide range of genotypes within and across species.…”
Section: Sorghummentioning
confidence: 99%
“…There are limited successes in enhancing crop yields under salinity stress as available knowledge of the mechanisms of salt tolerance has not been converted into useful selection criteria to evaluate a wide range of genotypes within and across species. Attempts have been made to evaluate salt tolerance at germination and emergence stages in grain sorghum (Igartua et al, 1994;, and large genotypic differences were reported, but this early evaluation appears to have little relation with overall performance under saline conditions (Munns et al, 2002;). Though Na+ exclusion and grain K+/Na+ ratios have been suggested to be reliable traits for selecting salt tolerant crops (Munns & James, 2003;Munns et al, 2002;Poustini & Siosemardeh, 2004;Netondo et al, 2004;), the value of that trait has not been used in a large scale.…”
Section: Sorghummentioning
confidence: 99%
“…Imposition of salt stress resulted in decreases in the percentage of seeds germinated (Almodares et al, 2007), although the strongest decline in germination occurred at the highest salt concentration (Table 2). Nevertheless, the development of high-yielding salinity tolerant sorghums is the best option to increase the productivity in soils (Igartua et al 1994). Similarly, Gill et al (2003) observed a great reduction in germination rate due to salt stress, in sorghum seeds at 37 •C in NaCl (−1.86MPa).…”
Section: Why Sweet Sorghum?mentioning
confidence: 99%
“…Cloruro de sodio (NaCl), sulfato de sodio, cloruro de calcio (CaCl 2 ), yeso (CaSO4), sulfato de magnesio, y cloruro de potasio, son las sales más comunes, reducen la tasa de germinación (Igartua et al, 1994), afectan el desarrollo de los cultivos (Maiti et al, 1994), su rendimiento (Macharia et al, 1994), la calidad del suelo y del agua, y eventualmente resulta en la erosión del sustrato y en la degradación del terreno (Rhoades y Loveday, 1990;Zhu, 2001), restringe el desarrollo radicular y finalmente causa la muerte de la planta. Según Almodares et al (2008a) los efectos inhibitorios de la salinidad sobre el crecimiento de la planta incluyen: a) toxicidad de iones; b) influencia osmótica; c) desbalance nutricional; el efecto conjunto de estos factores en la planta es la reducción de la eficiencia fotosintética de la planta y la disminución de la producción de biomasa.…”
Section: Introductionunclassified
“…Sodium chloride (NaCl), sodium sulfate, calcium chloride (CaCl 2 ), gypsum (CaSO4), magnesium sulfate and potassium chloride, are the most common salts, reduce the germination rate (Igartua et al, 1994), affecting crop development (Maiti et al, 1994), yield (Macharia et al, 1994), soil and water quality, and eventually results in soil erosion and land degradation (Rhoades and Loveday, 1990;Zhu, 2001) restricts root development and eventually kills the plant. According to Almodares et al (2008a) the inhibitory effects of salinity on plant growth include: a) ion toxicity; b) osmotic influence; and c) nutritional imbalance; the joint effect of these factors on the plant is the reduction of photosynthetic plant efficiency and decreasing biomass production.…”
Section: Introductionmentioning
confidence: 99%